Sport coaching concepts : a framework for coaching practice - Lyle, John; Cushion, Chris (London, England, UK ; New York, NY, USA : Routledge, Taylor & Francis Group, 2017)
"Coaching is a vital factor for success in sport at all levels. The book offers a comprehensive introduction to the theoretical issues that underpin sport coaching practice. It explains why a conceptual approach to sport coaching is more important than ever before, using practice-orientated analysis to help students develop a full understanding of coaching theory and practice."--Provided by publisher.
Developments in the field -- Developing a conceptual framework -- The coaching process -- Coaching domains and the role of the coach -- Expertise in sport coaching -- Modelling the coaching process -- A proposed model for coaching -- Operationalising the model, or, What coaches really do! -- Approaches to coaching : linking theory and practice -- Sport coaching in social context -- Coaching philosophy -- Pedagogy in practice -- The professionalisation of sport coaching -- Coach education and coaching practice -- Setting a research agenda.
Includes bibliographical references and index.
CoED
Text in English
Keywords: Coaching (Athletics) -- Great Britain